Analisis minat karir pada bidang perpajakan atas dasar motivasi, persepsi dan pengetahuan pajak - Reginalin Syukur, Faustina; Sitinjak, Norman Duma (Jurnal Ilmiah Bisnis dan Perpajakan (Bijak), 2025)
The growth of careers in the field of taxation in Indonesia is increasing in line with the government's efforts to optimize tax revenue through the implementation of the Coretax system. However, accounting students’ interest in pursuing a career in taxation remains relatively low. This study aims to analyze the influence of tax knowledge, motivation, and perception on students’ career interest in the taxation field. A quantitative approach was employed by distributing questionnaires to accounting students at Universitas Merdeka Malang. The results show that tax knowledge and perception have a positive influence on career interest in taxation, while motivation demonstrates an inconsistent effect, as supported by previous studies. These findings highlight the importance of improving the quality of tax education and fostering positive student perceptions toward taxation-related professions. The implications of this study can serve as a reference for higher education institutions in designing effective learning strategies and career guidance to prepare graduates who are ready to meet the future demands of tax professionals